Volcanism and Global Environmental Change - Schmidt, Anja; Fristad, Kirsten E.; Elkins-Tanton, Linda T. (Cambridge : Cambridge University Press, 2015)
Covering a key connection between geological processes and life on Earth, this multidisciplinary volume describes the effects of volcanism on the environment by combining present-day observations of volcanism and environmental changes with information from past eruptions preserved in the geologic record. The book discusses the origins, features and timing of volumetrically large volcanic eruptions; methods for assessing gas and tephra release in the modern day and the palaeo-record; and the impacts of volcanic gases and aerosols on the environment, from ozone depletion to mass extinctions. The significant advances that have been made in recent years in quantifying and understanding the impacts of present and past volcanic eruptions are presented and review chapters are included, making this a valuable book for academic researchers and graduate students in volcanology, climate science, palaeontology, atmospheric chemistry, and igneous petrology.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Global environmental change; Paleogeography; Paleoclimatology